VO #020 valuation of rebars welding and testing works connected to steel columns of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding VO #020 valuation of rebars welding and testing works connected to steel columns of BRAC University new campus project.